Effect of Optimum Utilization of Silica Fume and Lime On the Stabilization of Problematic Soils - Zaini, Muhammad Syamsul Imran; Hasan, Muzamir (International Journal of Integrated Engineering, 2023)
Chemically stabilized soil studies have revealed that the efficiency of stabilization is primarily depends on the natural environment of the soil. Because of its poor qualities, this sort of soil is classified as problematic. Expansive soils such as clay soil does not satisfy the standards for structural applications at this stage because its load applied from the building’s apex will be transmitted to the soil layers. This study aims at the soft kaolin clay stabilization by utilizing 4% and 6% of silica fume and several percentage inclusion of lime. The lime percentages of 3%, 5%, 7%, and 9%, whereas the ratio of silica fume is set at 4% and 6%. The primary goal of this study is to increase the shear strength of soft kaolin clay soil blended with 4% and 6% of silica fume (SF) and varying amounts of lime (L). The soil parameters were evaluated for soft kaolin alone and for 4% and 6% of silica fume blended with varying percentages of lime. The findings disclose that the optimal percentages of silica fume and lime in terms of maximum shear strength at 176.91 kPa of improvement were 4% and 7% respectively due to the pozzolanic reaction between silica fume and lime was more successful with soil particles. The combination of silica fume and lime blended with the soft kaolin clay can highly enhanced the strength and the internal friction angle of the soil compared to the lime and silica fume mixed alone. The optimal proportion for increasing the undrained shear strength and friction angle was 4% of silica fume and 7% of Lime which can cut costs, reduce environmental disturbance, and act as an eco-friendly substance in soil stabilization.